Earth's vanishing forests - Gallant, Roy A. (New York Macmillan Toronto Maxwell Macmillan Canada New York Maxwell Macmillan International, 1991)
Discusses the ecology of rain forests, the problem posed by the present danger to rain forests, and possibilities for the future.
Keywords: Rain forest ecology -- Juvenile literature; Deforestation -- Environmental aspects -- Juvenile literature; Nature -- Effect of human beings on -- Juvenile literature; Rain forest conservation -- Juvenile literature; Rain forest ecology; Rain forest conservation; Nature -- Effect of human beings on; Ecology